Design/empresa/sociedade - Landim, Paula da Cruz [UNESP] (Universidade Estadual Paulista (Unesp), 2009)
O presente trabalho se propôs a estudar, através de um levantamento sobre o estado da arte do ensino do design no Brasil, da sua prática pelos designers e da visibilidade das condições daí resultantes, discutir eventuais estratégias que tornem tanto o ensino como os seus produtos condizentes com a realidade nacional sem perda da universalidade. Os resultados estão fortemente subsidiados pelo estágio de pós-doutorado cumprido na Universidade de Arte e Design de Helsinque entre agosto de 2006 e maio de 2007

The present work brings a historical reflection of the Brasilian design and how the profession is adapting to cultural, temporal and technological changes. In other words, through a survey on the state of the art of the teaching of design, of its practice by the designers, and the visibility of the conditions resulting, discuss possible strategies to make the teaching of design, as their products, commensurate with the national reality without loss of the universality. At the same time, collecting subsidies for the discussion of the situation of the teaching of design and the development of strategies to enable their improvement, as a way to have appropriate professionals to the development of products that, although with the mark of our reality and culture, are also universal. The main objective of this research, was to verify how the academic training in the Brazilian design meets the expectations of society and the productive sector. The results are mainly subsidized by the research developed at UIAH - University of Art and Design in Helsinki, Finland, as a visitor researcher
Keywords: Desenho industrial; Mobiliario - Projetos; Mobiliário - Finlândia; Design